Rough computing theories, technologies, and applications - Hassanien, Aboul Ella 1964-; Suraj, Zbigniew 19XX-; Ślęzak, Dominik 1972-; Lingras, Pawan (Information Science Reference, 2008)
"This book offers the most comprehensive coverage of key rough computing research, surveying a full range of topics from granular computing to pansystems theory. With its unique coverage of the defining issues of the field, it provides libraries with a single, authoritative reference to this highly advanced technological topic" - Provided by publisher
Includes bibliographical references (p. 269-289) and index
Keywords: Soft computing; Rough sets; Soft Computing; Künstliche Intelligenz; Data Mining; Grobmenge; Aufsatzsammlung